Temporal and spatial variation of petroleum hydrocarbons and microbial communities during static release of oil pollution sediments - Li, Haoshuai; Sun, Hu; Wang, Xinping; Li, Fujuan; Cao, Lixin; Li, Yang; Dong, Ranran; Sun, Yuxiang; Sun, Peiyan; Bao, Mutai (Frontiers in Marine Science, 2022)
The migration and transformation of the petroleum hydrocarbons from sediments into water columns is an important basis for assessing the impact on marine environment. In this paper, a static release experiment of crude oils from the Bohai Sea was carried out to evaluate the temporal and spatial variation of petroleum hydrocarbons and microbial communities. The results showed C1 phenanthrene (C1-P) can be used as an evaluation index of different crude oils during static release of oil pollution sediments and their trends of the static release were similar. The crude oil with higher C1-P content released C1-P into the water body significantly higher. After 72 hours, the C1-P release degree of crude oil with a smaller viscosity was more obvious. In the crude oil with the smallest viscosity and the higher viscosity, the bacterial phyla abundance increase was greater. And more importantly, the top 10 abundance of the microbial communities in the water columns and sediments appeared partial (3 species) replacement phenomenon. The research results can deep understanding the migration and transformation of the petroleum hydrocarbons from oil pollution sediments and understanding of the interaction between extreme weather events and human activities by incorporating an eco-evolutionary perspective.